The Evaluation of Music Department Students of Institut Seni Indonesia Yogyakarta in Modes Identification - De'Vries Mau, Peter Angga Branco; Hapsari, Prima Dona (Resital: Jurnal Seni Pertunjukan, 2021)
Modes in Modality concept is a musical thinking that was used before 1600s. After 1600s (Baroque Era), the concept of modes changed into a contrast concept called Tonality (major-minor) and still exist today, in our era. Musical knowledge will evolve along with technological advances, but in fact there are so many composers today using the concept of modes to give another nuance and interpretation in their musical works. As academic musicians, surely the students of Music Department of ISI Yogyakarta got the concept of modes in several subject such as music theory, music structure and style, music analysis, and etc. However, the tonality concept that always used by common academic musicians today makes the concept of Modality become so hard to identify if they are heard a musical work that contains modes. This research will show us how many students of Music Department of ISI Yogyakarta who can’t identify a musical work that contains modes.